Understanding Gen Z Travel Behavior through Sustainable Destination Branding: A Conceptual Approach - Nurranto, Heri (Edusight International Journal of Multidisciplinary Studies, 2025)
In the digital and value-driven tourism landscape, destination image has emerged as a key determinant in shaping travel decisions, particularly among Generation Z. This conceptual study proposes an integrative model that links sustainable tourism practices and collaborative marketing strategies as foundational elements in developing an authentic and trusted destination image. Drawing from stakeholder theory, value co-creation, and the triple bottom line framework, the model addresses how sustainability narratives co-created by governments, businesses, communities, and travelers can influence trust, perceived authenticity, and ultimately, visit intention among Gen Z tourists. The framework positions destination trust and authenticity as mediators, while digital engagement and environmental consciousness act as moderating variables that reflect Gen Z’s digitally native and value-driven behavior. By synthesizing contemporary tourism, marketing, and consumer behavior theories, this study contributes to the development of sustainability-oriented destination branding. It also offers practical guidance for destination management organizations (DMOs) to design inclusive, narrative-based strategies that resonate with Gen Z values. Future empirical validation through structural equation modeling (SEM) is recommended to test the interrelationships proposed in the model